1995
DOI: 10.1037/0022-3514.69.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Predicting young adults' health risk behavior.

Abstract: A prototype model of risk behavior is described and was tested in a longitudinal study of 679 college students, beginning at the start of their freshman year. Perceptions of the prototype associated with 4 health risk behaviors (smoking, drinking, reckless driving, and ineffective contraception) were assessed along with self-reports of the same behaviors. Results indicated that prototype perception was related to risk behavior in both a reactive and a prospective manner. That is, perceptions changed as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
484
1
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(521 citation statements)
references
References 45 publications
24
484
1
8
Order By: Relevance
“…Both cigarette and alcohol use in adolescence were influenced by both intention to engage in the behavior, and willingness to do so. In support of the Prototype/Willingness model (Gibbons & Gerrard, 1995;Gibbons, et al, 2003;Gibbons, et al, 1998), both the intercept and slope of prototypes (social images of substance users) predicted cigarette use through willingness to smoke, and the intercept of prototypes predicted alcohol use through willingness to drink alcohol. In support of both the cognitive theories of Ajzen and Fishbein and of Gibbons and Gerrard, both the intercept and slope of subjective norms, or perceptions of friends' and classmates use, predicted use of both alcohol and cigarettes through both intentions and willingness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both cigarette and alcohol use in adolescence were influenced by both intention to engage in the behavior, and willingness to do so. In support of the Prototype/Willingness model (Gibbons & Gerrard, 1995;Gibbons, et al, 2003;Gibbons, et al, 1998), both the intercept and slope of prototypes (social images of substance users) predicted cigarette use through willingness to smoke, and the intercept of prototypes predicted alcohol use through willingness to drink alcohol. In support of both the cognitive theories of Ajzen and Fishbein and of Gibbons and Gerrard, both the intercept and slope of subjective norms, or perceptions of friends' and classmates use, predicted use of both alcohol and cigarettes through both intentions and willingness.…”
Section: Discussionmentioning
confidence: 97%
“…These processes have been brought together in the Prototype/Willingness (prototype) model of adolescent health behavior (Gibbons & Gerrard, 1995;Gibbons, Gerrard, & Lane, 2003;Gibbons, Gerrard, Blanton, & Russell, 1998). This model includes both the reasoned and planned path to behavior, through intentions, as outlined in the TRA and TPB, and a second less planful path to behavior through behavioral willingness.…”
mentioning
confidence: 99%
“…Thus, research and programs that keep individual women embedded within their relevant social contexts would seem to hold greatest promise. A number of studies have found investigation of factors such as interpersonal communication channels (Coleman, 1993), the social climate of a group (Cook, 1995), peer norms (Gwartney-Gibbs & Stockard, 1989), in-group social comparisons (Gibbons & Gerrad, 1995;Norris et al, 1995), and information about risk rates based in one's local community (Klepinger, Billy, Tanfer, & Grady, 1993) to be fruitful in shedding light on the social context within which risk perception is undertaken and to increase perceived self-relevance of risk. In a related vein, the preponderance of theorizing and findings related to risk perception in general and to acquaintance sexual aggression in particular have been based on samples containing little diversity with respect to socioeconomic status, racial or cultural heritage, religious affiliation, or other social group heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while these perspectives share health as a motivating concern (i.e., either the betterment of, or the fear or denial of risks to it), researchers have also uncovered a broader range of social psychological motives applicable to health decisions. Self-presentational motives (e.g., Leary et al, 1994) and appearance striving (Mahler, Kulik, Gerrard, & Gibbons, 2006), self-consistency (Stone, Aronson, Crain, Winslow, & Fried, 1994), social comparison (Gibbons & Gerrard, 1995), and a general need to protect the integrity of the self (Reed & Aspinwall, 1998;Sherman et al, 2000) have been implicated in decisions that affect health outcomes. These perspectives all recognize that motives not rooted in health can affect healthrelevant decisions and outcomes.…”
Section: Advances For Theorymentioning
confidence: 99%